Advanced polymeric materials : synthesis and applications - Rouxel, Didier; Thomas, Sabu; Kalarikkal, Nandakumar; Abdulrahman, Sajith T. (River Publishers, 2018)
Recent advances in polymer research have led to the generation of high quality materials for various applications in day to day life. The synthesis of new functional monomers has shown strong potential in generating novel polymer materials with improved properties. Advanced Polymeric Materials includes fundamentals and numerous examples of polymer blend preparation and characterizations. Developments in blends, polymer nanocomposites and its various characterization techniques are highlighted in the book.- Resumé vydavatele
Keywords: polymery; polymerizace; polymerní kompozitní materiály; polymers; polymerization; polymer composite materials; electronic books; papers of several authors; sborníky; elektronické knihy